P110 Symptomology and most bothersome symptoms among pediatric Crohn's disease and ulcerative colitis patients: Results from a physician and patient survey. (27th May 2021) - Dotson, J; Hunter, T; Lukanova, R; Crandall, W; Komocsar, W; Larkin, A; Meakin, S; Otley, A
Abstract: Background: Crohn's disease (CD) and ulcerative colitis (UC) are chronic gastrointestinal diseases, which often present during one's most productive years. The objective of this study was to assess the symptomology and most bothersome symptoms of pediatric CD and UC patients. Methods: Data from a cross-sectional survey of physicians and their pediatric CD and UC patients (age 2–17 years) conducted in France, Germany, Italy, Spain, United Kingdom, Japan, and United States were analyzed. Data were collected in 2019–2020 via physician-completed patient record forms and patient-self completed forms. Patients age 12–17 years completed their own questionnaires, while caregivers of younger children completed their respective questionnaires. Patient demographics and current symptoms were reported by physicians, while the most bothersome symptoms were reported by the patient/caregiver. All descriptive analyses were conducted for CD and UC patients separately. Results: Data from 1, 213 CD patients and 1, 162 UC patients were included in this analysis. CD patients had a mean age of 12.8 years, 59.5% were male, 75.5% were Caucasian and had a mean sPCDAI score of 10.7. Similarly, UC patients had a mean age of 12.9 years, 54.0% were male, 71.0% were Caucasian, and had a mean PUCAI score of 23.7. The majority of CD (94.9%) and UC patients (94.6%) were currently enrolled in school/education; however, 68.3% of CD and 61.1% of UC patients indicated that they have missed school/education because of their IBD symptoms. Abdominal pain was the most frequently reported symptoms among CD (41.9%) and UC (38.6%) patients. CD and UC patients reported abdominal pain, diarrhea, abdominal cramps, and bowel urgency as their most bothersome symptoms. Conclusion: Pediatric CD and UC patients experience multiple symptoms with the most bothersome symptoms being related to abdominal pain and bowel movements. These symptoms may impact pediatric CD and UC patients' daily lives and cause them to miss school.